A high-accuracy substructure method in the time domain for simulating pile-soil dynamic interaction in horizontal vibration. (December 2021) - Wang, Piguang; Zhang, Wenqian; Xu, Haibin; Zhao, Mi; Du, Xiuli
Abstract: An accurate and efficient substructure method in the time domain is developed to simulate pile-soil dynamic interaction during horizontal vibration. The present method considers the equilibrium of a linear elastic soil in both the radial and circumferential directions to account for three-dimensional wave scattering, and considers the end bearing pile as a one-dimensional rod. First, an analytical expression for the soil resistance to a horizontal vibration pile in the frequency-domain is obtained. From this, an exact dynamic stiffness relationship between the soil resistance and the pile displacement is constructed at the pile-soil interface. Further, the dynamic stiffness relationship in the frequency domain is transformed into a high-order approximation in the time domain. Then, this high-order approximation is equivalent to a mechanical model system consisting of mass, dashpot and spring elements. Finally, the effectiveness of the present method is verified and the effects of the dynamic stiffness of the soil on the dynamic responses of the pile are investigated.